2004
DOI: 10.4269/ajtmh.2004.70.8
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic and Clinical Indices of Malaria in a Semi-Immune Population of Western Thailand

Abstract: This study examines hematologic profiles of persons with acute Plasmodium falciparum or P. vivax infection in Maesod on Thailand's western border with Myanmar compared with febrile, non-parasitemic persons also reporting to malaria clinics. Nine hundred seventy-nine subjects were malaria-negative, 414 were infected with P. falciparum, and 646 were infected with P. vivax. Persons with patent parasitemia tended to have significantly lower white blood cell, red blood cell, platelet, and hemoglobin levels than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
202
8
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(256 citation statements)
references
References 27 publications
41
202
8
5
Order By: Relevance
“…In previous work, we reported differences between male and female participants that produce bimodal distributions in the patient populations (Erhart et al, 2004). The results shown here combine the sexes, but they also hold when the comparisons are made strictly among men or among women, with one exception.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 51%
See 2 more Smart Citations
“…In previous work, we reported differences between male and female participants that produce bimodal distributions in the patient populations (Erhart et al, 2004). The results shown here combine the sexes, but they also hold when the comparisons are made strictly among men or among women, with one exception.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 51%
“…Because differences between the Coulter and QBC systems may have confounded analyses of reported densities , we did not pursue comparisons between sites. Detailed hematologic data were collected only in 2001 (Erhart et al, 2004). We used the Mann-Whitney U-test and Spearman's rank correlation coefficient to compare distributions (Sokal and Rohlf 1981), and give P values for 2-tailed tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted by Erhart LM et al, Jadhav UM et al, vivax was the most common species while Bashawri LAM et al reported higher falciparum prevalence. 3,16,17 In India, vivax is the most common species encountered followed by falciparum. However, in recent years there has been an upswing in the falciparum cases.…”
Section: Discussionmentioning
confidence: 99%
“…3,16,17 Thrombocytopenia is a common finding in cases of malaria both vivax and falciparum as shown by most of the studies conducted. In the present study thrombocytopenia was seen in 71% of all malaria cases.…”
Section: Studiesmentioning
confidence: 99%